Efficient oupling of nanoparticles to electrochemically exfoliated graphene - Wei, Wei; Wang, Gang; Yang, Sheng; Feng, Xinliang; Muellen, Klaus (Journal of the American Chemical Society, 2015)
Electrochemically exfoliated graphene (EEG) is a new generation of high-quality graphene that holds great promise for the construction of hybrid materials. However, the assembly of EEG hybrids with well-defined nanostructures has remained a major challenge. In this study, we demonstrate a bottom-up approach toward the assembly of EEG sheets with a series of functional nanoparticles (Si, Fe3O4, and Pt NPs) into two-dimensional sandwich-like hybrid nanostructures. Polyaniline in the emeraldine base form functions as a versatile dopant to couple NPs onto EEG through either electrostatic interactions or hydrogen bonding. This protocol enables processing and assembly of EEG using an economical pathway, for which we further demonstrate the potential application of EEG-Si hybrids as high-performance anode material for lithium storage.
CRIS-Team Scopus Importer:2023-03-20